Fatty acid composition of common bugle herb (Ajuga reptans L.) - Grytsyk, Andriy; Maliuvanchuk, Svitlana (ScienceRise: Pharmaceutical Science, 2019)
Aim. Identification and determination of the qualitative composition and quantitative content of fatty acids in the grass of Ajuga reptans. Methods of the research. The study of Ajuga reptans fatty acids was carried out by gas chromatography-mass spectrometry, which is based on the formation of fatty acid methyl esters with their subsequent determination. Results. The method of chromatography-mass spectrometry was the first to study the fatty acid composition of (Ajuga reptans L.). As a result of a study in the herb of Ajuga reptans , 22 substances were identified, of which 9 fatty acids were identified. The quantitative content was dominated by polyunsaturated fatty acids - linolenic and linoleic and saturated - palmitic. Their total content in terms of the sum of fatty acids was 56.71 % (unsaturated), 28.18 % saturated. A small amount of following substances was detected - stearic, eicosanoic, tetracosanoic, behenic acid (6.65 %). Conclusions. Fatty acids are important biocompounds, which are involved in complex metabolic processes, are important components of lipids and cell membranes in the form of phospholipids, thereby have a large biological role. Unsaturated fatty acids were found in significant quantities in the herb of common bugle, the amount of which was 4706.78 mg / kg, which was almost 1.4 times higher than the amount of saturated fatty acids (3380.83 mg / kg). The research results can be used in the development of quality control methods for common bugle raw materials and the preparation of biologically active substances from the studied raw materials